Effectiveness of employee engagement for DHL Worldwide Express Bangladesh Pvt. Ltd. - Preema, Tahseen Labeeba (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.